RESEARCH OF WEAR AND INCREASING WEAR RESISTANCE OF THE WORKING PART OF BUSBAR PUNCHING TOOLS BY SURFACING METHOD - Mussayev, Medgat; Sherov, Karibek; Kassymbabina, Dana; Abdugaliyeva, Gulnur; Donenbayev, Bakytzhan; Kardassinov, Sayat; Karsakova, Nurgul; Tussupova, Sayagul (Journal of Applied Engineering Science, 2024)
This article aims to establish the cause of wear and select a surfacing method to increase the wear resistance of the working part of the busbar punching tool. A study was carried out on existing methods for increasing the wear resistance of working surfaces of parts and tools operating under heavily loaded thermodynamic conditions, as well as under high contact and impact loads. As a result of the data analysis, the ESAB OK Tubrodur 35GM surfacing wire and the mechanized surfacing method using a protective gas environment were selected for surfacing the working part of the busbar punching tool. An experiment was planned to determine the number and parameters of experiments that will allow achieving the required level of accuracy to obtain the necessary information about the object of study. Calculations made during the experiment’s planning resulted in a multiple regression equation that determines the dependence of the deposited layer’s hardness on the current strength, welding voltage, and the speed of movement of the welding torch. The optimal operating parameters for surfacing samples in shielding gases were determined using the MATLAB software package. The research, the results of which are presented in this article, is funded by the Committee on Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan (grant № AP19578884 "Increasing wear resistance and improving the design of the tool of the busbar punching machine").